The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1983-40632021v5167054
|View full text |Cite
|
Sign up to set email alerts
|

Production, water-use efficiency and post-harvest quality of hydroponic mini watermelon under salinity stress1

Abstract: Irregularity or shortage of rainfall in semi-arid regions forces farmers to use low-quality water to irrigate crops. The present study aimed to assess the water-use efficiency and post-harvest quality of ‘Sugar Baby’ mini watermelon in response to different electrical conductivities of the nutrient solution [2.5 (control), 3.5, 4.5, 5.5 and 6.5 dS m-1], in a floating hydroponic system. The experimental design was completely randomized, with four replicates. The water consumption, production and water-use effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Concerning the characteristics of the chemical quality of watermelon fruits, the obtained results demonstrated that increasing water salinity levels resulted in gradual increments in total soluble solids (TSS), total sugars, lycopene content and titratable acidity. The results are in good accordance with several studies which showed that higher salinity levels reduced water uptake in the salt stressed plants and thus improved fruit quality by increasing the soluble solids, sugar content and acidity (Sousa et al 2016, Simpson et al 2018, Ramezan et al 2020, Cova et al 2021. Moreover, the increase in total soluble solids and total sugars of watermelon fruits due to salt stress may reflect an osmotic adjustment obtained by enhanced synthesis of soluble organic compounds in the plant tissue (Simpson et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Concerning the characteristics of the chemical quality of watermelon fruits, the obtained results demonstrated that increasing water salinity levels resulted in gradual increments in total soluble solids (TSS), total sugars, lycopene content and titratable acidity. The results are in good accordance with several studies which showed that higher salinity levels reduced water uptake in the salt stressed plants and thus improved fruit quality by increasing the soluble solids, sugar content and acidity (Sousa et al 2016, Simpson et al 2018, Ramezan et al 2020, Cova et al 2021. Moreover, the increase in total soluble solids and total sugars of watermelon fruits due to salt stress may reflect an osmotic adjustment obtained by enhanced synthesis of soluble organic compounds in the plant tissue (Simpson et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Increasing the salinity of the irrigation water reduced rind thickness and fruit mass by 8.80% and 5.7%, respectively for hydroponic mini watermelons in a floating hydroponic system, per unit increase in water conductivity (dS m −1 ). [ 67 ] In a hydroponic system for basil production, using a saline nutrient solution (40 and 80 mmol L −1 NaCl) reduced water consumption, growth, phytomass production, and the absolute growth rate of basil. [ 68 ] In regions with a high salinity of water resources, MDCs can help in relieving the salinity problem to establish hydroponic agriculture systems.…”
Section: Discussionmentioning
confidence: 99%